Metabolism in Patients with Rheumatoid Arthritis: Resting Energy Expenditure, Physical Activity and Diet-Induced Thermogenesis. Invited Review - Metsios, Giorgos S.; Stavropoulos-Kalinoglou, Antonios; Panoulas, Vasileios F.; Koutedakis, Yiannis; Kitas, George D. (Recent Patents on Endocrine, Metabolic & Immune Drug Discovery (Discontinued), 2008)
Metabolism is one of the most important physiological functions. Resting energy expenditure, physical activity and diet are the main factors of total metabolism but the contribution of these components to total energy expenditure may be significantly changed with chronic inflammatory diseases such as rheumatoid arthritis (RA). RA is a disease that alters normal metabolism due to the overproduction of pro-inflammatory cytokines and may lead to rheumatoid cachexia. This review focuses on the individual components of total energy expenditure and discusses how physical activity and diet may influence resting metabolism both in the healthy population as well as patients with RA. Moreover, information is provided regarding the available patents (i.e. equipment and prediction equations) that may be used in order to predict metabolism in the normal population and RA patients.
Keywords: fat mass